Model of factors affecting active learning behavior: Context of three southern border provinces of Thailand - Ha, Rudiyah; Hussien, Suhailah; Wae-U-seng, Niloh; Hengpiya, Abdulhakam (Political Science Association of Kasetsart University Bangkok, Thailand, 2017)
The purpose of this paper is to examine the structure of factors affecting active learning behavior for Islamic studies students’ in three southern border provinces of Thailand. Data were collected from 300 undergraduate students by using a questionnaire. The samples were from three universities in three southern border provinces of Thailand. The Structural Equation Modelling (SEM) was employed to develop the model. Exploratory factor analysis and confirmatory factor analysis were utilized to identify the underlying factors and test the construct reliability and convergent validity. The results show that the factors affecting active learning behavior (FAALB) model was found to be fit and reliable and all parameter estimates was a valid construct, the values of TLI, CFI, IFI and NFI were more than the cut-off point, the X2/df and RMSEA also achieved the suggested value. The study found evidence that active learning behavior is influenced by psychological states.